Performance of Azolla pinnata fern protein hydrolysates as an emulsifier and nutraceutical ingredient in an O/W emulsion system and their effect on human gut microbiota and mammalian cells - Qoms, Mohammed S.; Arulrajah, Brisha; Wan Ibadullah, Wan Zunairah; Ramli, Nurul Shazini; Chau, De-Ming; Sarbini, Shahrul Razid; Saari, Nazamid (Royal Society of Chemistry, 2024)
This study investigated the dual potential of Azolla pinnata fern protein hydrolysates (AFPHs) as functional and nutraceutical ingredients in an oil/water emulsion system. The AFPH-stabilised emulsion (AFPH-E) displayed a small and uniform droplet distribution and was stable to aggregation and creaming over a wide range of pH (5-8), salt concentrations ≤ 100 mM, and heat treatment ≤ 70 °C. Besides, the AFPH-E possessed and maintained strong biological activities, including antihypertensive, antidiabetic, and antioxidant, under different food processing conditions (pH 5-8; NaCl: 50-150 mM, and heat treatment: 30-100 °C). Following in vitro gastrointestinal digestion, the antihypertensive and antioxidant activities were unchanged, while a notable increase of 8% was observed for DPPH. However, the antidiabetic activities were partially reduced in the range of 5-11%. Notably, AFPH-E modulated the gut microbiota and short-chain fatty acids (SCFAs), promoting the growth of beneficial bacteria, particularly Bifidobacteria and Lactobacilli, along with increased SCFA acetate, propionate, and butyrate. Also, AFPH-E up to 10 mg mL−1 did not affect the proliferation of the normal colon cells. In the current work, AFPH demonstrated dual functionality as a plant-based emulsifier with strong biological activities in an oil/water emulsion system and promoted healthy changes in the human gut microbiota.